Gênero e suas manifestações na primeira infância: um estudo com crianças de 21 a 30 meses de idade - Paludeto, Simone Priscila (2010)
Sex is genetically inherited, but the child's participation in a particular social and cultural group must be built. Previous studies suggest that between 16 and 24 months old the child already has notions of gender identity, being able to categorize objects culturally appropriate to males and females. This research investigates the manifestations of gender identity in children between 21 and 30 months of age under the influence of the company of another child of the same sex or opposite sex. This study proposed to verify two hypotheses. The first is that children are influenced by the sex of their child partner selecting and manipulating objects. The second is that if this mentioned gender reference exists between boys and girls, the manifestation of imitative behavior will be influenced by the gender of the child partner. 12 children between 21 and 30 months old participated in the experiment, six boys and six girls, medium to high social-economic level. Dyads were formed using children of the same gender and children of mixed gender. The procedure consisted of placing the dyads of children in the presence of toys, some of them suitable for boys and other suitable for girls, and watch their choices and imitations. Each child dyad was videotaped during 20 minutes in the presence of objects considered appropriate for males and females. The following were analyzed: objects chosen by children, imitative behavior and time of manipulation of objects. The study showed that child s choices and objects manipulations were influenced by their partners. In dyads exclusively male prevail the manipulation of objects appropriate to the male gender, and in exclusively female dyads prevail the manipulation of objects appropriate to the female gender. However the frequency of choice and manipulation of female objects by male children increased in mixed dyads. With respect to imitation, the boys showed a greater tendency to imitate the girls than girls to imitate the boys